Structural and functional properties of meprin β metalloproteinase with regard to cell signaling - Li, Wenjia; Lueckstaedt, Wiebke; Wöhner, Birte; Bub, Simon; Schulz, Antonia; Socher, Eileen; Arnold, Philipp (Biochimica Et Biophysica Acta-Molecular Cell Research, 2021)
The metalloproteinase meprin β plays an important role during collagen I deposition in the skin, mucus detachment in the small intestine and also regulates the abundance of different cell surface proteins such as the interleukin-6 receptor (IL-6R), the triggering receptor expressed on myeloid cells 2 (TREM2), the cluster of differentiation 99 (CD99), the amyloid precursor protein (APP) and the cluster of differentiation 109 (CD109). With that, regulatory mechanisms that control meprin β activity and regulate its release from the cell surface to enable access to distant substrates are increasingly important. Here, we will summarize factors that alternate meprin β activity and thereby regulate its proteolytic activity on the cell surface or in the supernatant. We will also discuss cleavage of the IL-6R and TREM2 on the cell surface and compare it to CD109. CD109, as a substrate of meprin β, is cleaved within the protein core thereby releasing defined fragments from the cell surface. At last, we will also summarize the role of proteases in general and meprin β in particular in substrate release on extracellular vesicles.
Keywords: meprin β; CD109; proteolysis; metalloproteases; substrates; extracellular vesicles